Free radical scavenging and antibacterial activity of crude extracts from selected plants of medicinal value used in Zululand - Muleya, Eddwina; Ahmed, A.S.; Sipamla, A.M.; Mtunzi, F.M. (Asian Network for Scientific Information, 2016)
Ledebouria revoluta, Berkheya setifera and Carissa bispinosa are some of the medicinal plants used in South African traditional medicine. An investigation to evaluate antimicrobial, anti-inflammatory and free radical scavenging activities of the root crude extracts and fractions from the three plants was carried out. Reduction by 2, 2-azinobis (3-ethylbenzothiazoline)-6-sulfonic acid (ABTS.+) and 2, 2-di (4-tertoctylphenyl)- 1-picrylhydrazyl (DPPH.) radicals were used to assess antioxidant capacities by change in absorbance in a UV-VIS spectrophotometer. Anti-inflammatory activity of the plant extracts against 15- soybean derived lipoxygenase (15-LOX) enzyme was evaluated as increase in absorbance at 234 nm after addition of soya bean derived 15-LOX, using linoleic acid (134 μM) as substrate. Anti-microbial activities were determined by assessing the plant samples’ Minimum Inhibitory Concentrations (MICs) by a micro dilution method. Carissa bispinosa and Berkheya setifera have shown good to moderate antimicrobial activity. Ledebouria revoluta displayed good activities (20 μg/mL) for both acetone and methanol fractions against E. coli and good-moderate activity (160-320 μg/mL) against the rest of the bacterial strains used. Anti-fungal activity for Ledebouria revoluta methanol fraction (20 μg/mL) is high against Candida albicans. Percentage inhibition of 15-soybean lipoxygenase enzyme by the crude extracts at concentration of 25 μg/mL was for Berkheya setifera, 80%, Carissa bispinosa, 65% and Ledebouria revoluta, 40%.